2022
DOI: 10.3390/molecules27103100
|View full text |Cite
|
Sign up to set email alerts
|

HCnH− Anion Chains with n ≤ 8 Are Nonlinear and Their Permanent Dipole Makes Them Potential Candidates for Astronomical Observation

Abstract: To be detectable in space via radio astronomy, molecules should have a permanent dipole moment. This is the plausible reason why HCnH chains are underproportionally represented in the interstellar medium in comparison with the isoelectronically equivalent HCnN chain family, which is the most numerous homologous series astronomically observed so far. In this communication, we present results of quantum chemical calculations for the HCnH family at several levels of theory: density functional theory (DFT/B3LYP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
3
5
0
Order By: Relevance
“…Tables 1, S2, and S3) we performed unrestricted (UB3LYP) calculations. Therefore, it is worth mentioning that, similar to other similar cases [19, 20, 21, 22], we can safely rule out spin contamination artifacts (cf. Table 1).…”
Section: Computational Detailssupporting
confidence: 65%
“…Tables 1, S2, and S3) we performed unrestricted (UB3LYP) calculations. Therefore, it is worth mentioning that, similar to other similar cases [19, 20, 21, 22], we can safely rule out spin contamination artifacts (cf. Table 1).…”
Section: Computational Detailssupporting
confidence: 65%
“…Most importantly from astrochemical perspective (see our preliminary report [ 88 ] and Section 2.5 for further details), we found that, irrespective of their parity, linear HC n H − anion conformers with n8$n \le 8$ are unstable against molecular vibrations, that is, not all computed vibrational frequencies are real. Our calculations showed that cis and trans (C 2 v and nearly C 2 h symmetry, respectively) anion HC n H − nonlinear conformers with n8$n \le 8$ (like those depicted in Figure ) correspond to structures wherein all vibrational frequencies are real.…”
Section: Resultsmentioning
confidence: 84%
“…To understand why the results presented in this paper for HC n H − anions —partially reported recently [ 88 ] —are important from an astrochemical perspective, one should first note that both neutral HC n H 0 and cation HC n H + are linear chains possessing inversion symmetry. Their Dh$_{\infty h}$ symmetry is incompatible with a permanent dipole moment (μ0$\mu \equiv 0$).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The solvent (water) was treated within the polarized continuum model (PCM) [31] using the integral equation formalism (IEF) [32]. Similar to other cases studied recently [33][34][35], spin contamination did not appear to be an issue for the unrestricted spin (UB3LYP) approaches, as witnessed by the values of the total spin values S 2 before and after annihilation of the first spin contaminant presented in the following. For reasons explained below, we also performed restricted open shell (ROB3LYP) calculations, which are more demanding computationally for larger molecules.…”
Section: Computational Detailsmentioning
confidence: 60%